IMPLEMENTASI TECHNOLOGY ACCEPTANCE MODEL DALAM AKTIVITAS BERBELANJA ONLINE MELALUI SITUS LAZADA.CO.ID - Marlina, Erlin; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Some research indicates that online site user behavior has an important role to the successful implementation. The presence of online sale and purchase site Lazada.co.id with various innovations bring the impacts in the life of society both positive and negative. In addition, changes in the pattern of shopping for people who were still conservative, now slowly began to switch online shopping, because of the ease of transactions, goods offered more diverse, competitive prices, and can be done anywhere and anytime. This study aimed to examine the effect among variables at the Technology Acceptance Model on the online site Lazada.co.id.Respondent in this study were 166 online site users Lazada.co.id in Pekanbaru. How to determine the number of samples using snowball because the absence of data on the number of consumers use of online sites. Use traditional methods of data collection questionnaire. Data were analyzed using Structural Equation Model (SEM) with AMOS software program. Based on the literature review, the research model using the Technology Acceptance Model (TAM) with variable perceived ease of use, perceived usefulness, attitude toward using, behavioral intention to use dan acceptance.The results of this study indicate the variables perceived ease of use has a positive and significant effect on the variable attitude toward using the total influence of 0,341. Variable perceived usefulness has a positive and significant effect on the variable attitude toward using the total influence of 0,331. Variable perceived ease of use has a positive and signifikan effect on the variable behavioral intention to use and has a total effect of 0,295. Variable perceived usefulness has a positive and significant effect on the variable behavioral intention to use the total influence of 0,499. Variable attitude toward using has a positive and significant effect on the variable a behavioral intention to use the total influence of 0,780. Variable behavioral intention to use has a positive and significant effect on the variable acceptance the total influence of 0,341.Key Word: Lazada.co.id, Technology Acceptance Model (TAM), Structural Equation Model (SEM)